2020
DOI: 10.1186/s12879-020-05064-w
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Enterobius vermicularis infection on biochemical parameters in the blood of children in Erbil Province, Iraq

Abstract: Background: Enterobius vermicularis is an intestinal helminthic parasite that causes a gastrointestinal infection called enterobiasis. Children are more susceptible to infection than adults. The current study aimed to explore the prevalence of E. vermicularis infection among children in Erbil City concerning demographic factors and certain blood parameters. Methods: A cross-sectional and analytical study was conducted on 505 children (3-10 years). Cellophane tape samples and blood samples were taken from parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
10
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 17 publications
5
10
0
3
Order By: Relevance
“…Serum iron declined significantly in E. vermicularis infected group as compared to non-infected group. The decrease in serum iron concentrations is likely because of appetite loss that may be a result of E. vermicularis infection [21]. This result is similar to that reported by others [35,36].…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Serum iron declined significantly in E. vermicularis infected group as compared to non-infected group. The decrease in serum iron concentrations is likely because of appetite loss that may be a result of E. vermicularis infection [21]. This result is similar to that reported by others [35,36].…”
Section: Discussionsupporting
confidence: 89%
“…There have been many studies that reported the epidemiological and demographic status of E. vermicularis among the population from different parts of Iraq [16][17][18]. In addition, some other investigators focused on enterobiasis and its relation to enuresis, anaemia, biochemical parameters of the blood, and vitamin deficiencies [19][20][21]. Although several studies were achieved regarding E. vermicularis, updating our knowledge is still needed about its potential influence on the haematological, nutritional status, and immunological status of the host infected with E. vermicularis.…”
mentioning
confidence: 99%
“…Enterobiasis caused by Enterobius vermicularis infection is widely distributed around the world [ 1 , 2 ]. Transmission usually occurs among children in childcare agencies and kindergartens [ 3 , 4 , 5 ]. The main symptoms of enterobiasis include perianal skin itching, night terrors, grinding of teeth, irritability, anorexia and emaciation, but it may also cause appendicitis and urogenital system inflammation due to ectopic parasitism [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Enterobius vermicularis (needle worm, thread worm or chair worm) is one of the nematode worms that has more geographical distribution than other worms [1]. It is estimated that at least 200 million people worldwide, especially children, are infected each year [2]. The prevalence of E. vermicularis infestation is associated with poor environmental hygiene, inadequate personal hygiene, and contaminated food [3].…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have been performed on the relationship between the prevalence of E. vermicularis in children with sex, age, demographic and geographical factors, blood and immunological factors [2]. However, psychological and IQ tests in children have not been performed.…”
Section: Introductionmentioning
confidence: 99%